AFF Architekten: Creative Processes For A Social Architecture - Anna Rosellini (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2020)
In progressing towards architecture that strives to make itself accessible to the people, AFF Architekten have come across testimonies of life and traces of past times. They have initiated a true collection of disparate objects, stacked on shelves, and of photographs taken, printed and classified by subject in folders.